The expanding roles of Nr6a1 in development and evolution - Li, Jingxuan; Mascarinas, Pauline; McGlinn, Edwina (Frontiers in Cell and Developmental Biology, 2024)
The Nuclear Receptor (NR) family of transcriptional regulators possess the ability to sense signalling molecules and directly couple that to a transcriptional response. While this large class of proteins are united by sequence and structural homology, individual NR functional output varies greatly depending on their expression, ligand selectivity and DNA binding sequence specificity. Many NRs have remained somewhat enigmatic, with the absence of a defined ligand categorising them as orphan nuclear receptors. One example is Nuclear Receptor subfamily 6 group A member 1 (Nr6a1), an orphan nuclear receptor that has no close evolutionary homologs and thus is alone in subfamily 6. Nonetheless, Nr6a1 has emerged as an important player in the regulation of key pluripotency and developmental genes, as functionally critical for mid-gestational developmental progression and as a possible molecular target for driving evolutionary change in animal body plan. Here, we review the current knowledge on this enigmatic nuclear receptor and how it impacts development and evolution.